DEFORMATION RELIEF AS AN INDICATOR OF REBINDER EFFECT - Karuskevich, Mikhail; Maslak, Tatiana; Seidametova, Gulzar (Proceedings of National Aviation University, 2013)
The paper presents the results of a research directed on the creating the method of assessing the impact of surfactants on the fatigue of aluminum alloys. The possibility of the Rebinder effect investigation by the deformation relief of the surface, emerging and developing as a result of cyclic loading, is shown. Anti-corrosion and lubricating materials, widely used in aviation, are selected as surfactants. The effect of surfactants on the incubation stage of fatigue is established.